2016
DOI: 10.1111/flan.12195
|View full text |Cite
|
Sign up to set email alerts
|

Mutually Beneficial Foreign Language Learning: Creating Meaningful Interactions Through Video‐Synchronous Computer‐Mediated Communication

Abstract: Providing learners of a foreign language with meaningful opportunities for interactions, specifically with native speakers, is especially challenging for instructors. One way to overcome this obstacle is through video‐synchronous computer‐mediated communication tools such as Skype software. This study reports quantitative and qualitative data from a Skype partner program that emphasized meaningful communication between American students learning Japanese in the United States and Japanese students learning Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 11 publications
2
42
0
Order By: Relevance
“…The Skype program in which students participated over the 3‐year period under consideration (2015–2017) has been described in Kato et al (). Apart from minor changes each year, described in the following paragraph, the overall scheduling pattern, general requirements, pre and post speaking tests, questionnaires, and postprogram reflection prompts remained the same.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Skype program in which students participated over the 3‐year period under consideration (2015–2017) has been described in Kato et al (). Apart from minor changes each year, described in the following paragraph, the overall scheduling pattern, general requirements, pre and post speaking tests, questionnaires, and postprogram reflection prompts remained the same.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a longitudinal cross‐sectional study by Saito, Dewaele, Abe, and In'nami () found that “more frequent L2 use with positive emotions directly impacts acquisition” (p. 709), including speaking skills. Although enjoyment is likely to lead to increased interest in maintaining the conversation partnership beyond a specific course or program (Kato et al, ) and although several studies focusing on VSMC found students’ levels of enjoyment to be important enough to report (e.g., Yang et al, ; Yanguas, ), none attempted to determine if enjoyment was correlated with improvement in oral abilities.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations